Analisis Keterkaitan Cadangan Karbon dengan Penyerapan CO2 dan Pelepasan O2 pada Tutupan Lahan Hutan Sekunder dan Kelapa Sawit di Kabupaten Luwu Timur - Karuru, Sakti Swarno; Rasyid, Burhanuddin; Millang, Syamsuddin (Universitas Hasanuddin, 2020)
This study aims to describe the linkage of carbon stocks in secondary forest and oil palm land cover to the amount of CO2 absorbed and the release of O2 to estimate carbon stocks in land cover in secondary forest and oil palm. The research use sample plot size 20 x 50 that taken 9 times for each land cover. Biomass data was collected using non-destructive sampling, since for undergrowth and necromass using destructive sampling by cutting and taking all the undergrowth and litter that are in a 1 x 1 meter quadrant. There are two kinds of soil sampling that collected; disturbed soil and intact soil. The results showed that the ability of each type of plant had varying values ​​of carbon stock, CO2 absorption and oxygen release on land cover. The value of carbon stock, CO2 absorption and oxygen release respectively on land cover, namely on secondary forest land cover is 265.86 tons / ha, 974.82 tons / ha and 708.96 tons / ha and oil palm is 100.89 tons / ha, 369.93 tons / ha and 269.04 tons / ha.